ANALISIS TINGKAT KEKUATAN OTOT DAN DAYA TAHAN KARDIORESPIRASI DENGAN PRESTASI PORPROV JAWA TENGAH ATLET PUSAT LATIHAN KABUPATEN JEPARA - Ulil Abshor; Anam, Khoirul; Setiowati, Anies; Indardi, Nanang; Abshor, Ulil (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2024)
This study aims to determine the relationship between muscle strength and cardiorespiratory endurance with the performance of PORPROV Central Java athletes at the Jepara Regency training center. This research uses a quantitative descriptive approach with the Secondary Data Analysis (ADS) method. The sample used was 50 athletes. Researchers used data collection techniques through secondary data obtained from KONI Jepara Regency. Based on the data analysis carried out, the results obtained were that for muscle strength there were 37 athletes who excelled with an average of 149.3751 > 68.51846. Meanwhile, there were 13 athletes who did not excel with an average of 177.8538 > 86.51366, the average value was greater than the standard deviation so the data had small variations and could be said to be good. It can be seen that the significant value is 0.00 < 0.05, which means that the data is significant. In cardiorespiratory endurance, there were 37 athletes who excelled with an average of 17,543 > 43,631. Meanwhile, there were 13 athletes who did not excel with an average of 16,519 > 28,895, the average value was greater than the standard deviation so the data had small variations and could be said to be good. It can be seen that the significant value is 0.00 < 0.05, which means that the data is significant.